Preparation of high performance conductive Polyaniline Magnetite (PANI/Fe3O4) nanocomposites by sol-gel method - Takai, Zakiyyu Ibrahim; Mustafa, Mohd K.; Asman, S. (Asian Journal of Jurnal of Chemistry, 2018)
The conductivities of polyaniline magnetite (PANI/Fe3O4) nanocomposites prepared by sol-gel method were measured by standard van der Pauw DC 4-point probe method. PANI/Fe3O4 conductivity was measured as a function of wt % (5, 10, 15, 20 and 25 wt %) of Fe3O4 nanoparticles. It was observed that the conductivity of polyaniline containing certain percentage of Fe3O4 nanoparticles is slightly lower than the bulk PANI nanotubes and drastically decreases with increase of wt % Fe3O4 nanoparticles. The high conductivities of PANI/ Fe3O4 nanocomposites was observed due to high concentration of dopant (oxidants) used in the polymerization process and the optimization of these composites allows this being use as a parameter for the production of nanofibers. Fourier transform infrared spectra, field emission scanning electron microscope, X-ray diffraction and ultraviolet-visible absorption spectra are used to characterize the phase structure, morphologies and functional group of the PANI/Fe3O4 composites samples. Fourier transform infrared analysis indicates the presence of PANI containing Fe3O4 nanoparticles and the field emission scanning electron microscope (FESEM) results has proven that the formation of nanofibers in the PANI/Fe3O4 nanocomposites. The crystalline phase of PANI/Fe3O4 nanocomposites studied by X-ray diffraction indicated that the Fe3O4 nanoparticles was present in the PANI matrices.